EXAMINATION OF SPERMATOZOA IN LABORATORY CONDITIONS AND THEIR CHARACTERISTICS - Allamuratova Miyasar Kuralbay qizi; Kurbanova Z. Ch; Hakimov S.A (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: The aim of this study is to examine spermatozoa under laboratory conditions and determine their characteristics. The morphology, microscopic structure, motility level, and biochemical properties of spermatozoa, including ATP levels, are analyzed using laboratory methods. The results of the research contribute to forming scientific foundations for evaluating spermatozoa function in the fields of reproductive biology and clinical diagnostics.